Architecture of Accountability and the Rule of Law in Public Finance in Kosovo: the Impact of the Auditor General - Nur Çeku (LeXonomica, 2021)
Accountability and the rule of law are fundamental and indispensable elements of democracy. The legitimacy and transparency of the collection and spending of public finances is a sine qua non of democratic governance. To ensure this, it is necessary to take legal action and find specialized mechanisms that have the authority to exercise control and prevent possible abuse of power. These mechanisms are an integral part of the architecture of economic governance and most countries have designed the institution of the Auditor General as the best way to achieve this goal. This institutional mechanism ensures financial and legal control as well as a performance appraisal of the government. Therefore, this paper analyzes the development of the Auditor General in Kosovo, discusses the legal framework and its relation with other branches of government, and also examines the challenges and prospects in implementing its recommendations from the public sector in the future.Povzetek. Odgovornost in pravna država sta temeljna in nepogrešljiva elementa demokracije. Zakonitost in preglednost zbiranja in porabe javnih financ sta nujna pogoja demokratičnega upravljanja. Da bi to zagotovili, je treba sprejeti pravne ukrepe in poiskati specializirane mehanizme, ki imajo pooblastila za izvajanje nadzora in preprečevanje morebitnih zlorab oblasti. Ti mehanizmi so sestavni del arhitekture gospodarskega upravljanja in večina držav je zasnovala institucijo generalnega revizorja kot najboljši način za dosego tega cilja. Ta institucionalni mehanizem zagotavlja finančni in pravni nadzor ter oceno uspešnosti vlade. Zato ta članek analizira razvoj institucije generalnega revizorja na Kosovu, obravnava pravni okvir in njegov odnos z drugimi vejami oblasti ter proučuje izzive in možnosti pri izvajanju njegovih priporočil v javnem sektorju v prihodnosti.